Perspectives of Development of Low Emission Zones in Poland: A Short Review - Kowalska-Pyzalska, Anna (Frontiers in Energy Research, 2022)
Introduction of low emission zones (LEZ) in many cities is supposed to mitigate negative externalities from urban transportation, such as noise and GHG emissions. LEZ are present in most of Western European countries, but in Eastern and Central Europe they are rare, even though in this part of Europe the air quality norms in the cities are very often exceeded. The experience from many countries proves that introduction of LEZ should be preceded with the examination of social acceptance to forecast and overcome the potential barriers of adoption to new rules and regulations. It is especially important in country like Poland, where LEZ are going to be introduced in the coming future. Hence, this paper aims to review the factors responsible for social acceptance of LEZ as well as to discuss the prospects of establishing LEZ in Poland in the light of the experiences of other countries, urban and transport challenges in Polish cities, as well as legislative, economic and social aspects. The results of the study are presented by means of SWOT analysis, showing that well thought-out solutions and the gradual introduction of restrictions in car traffic can have a positive impact on the level of social acceptance and behavioral change. Measuring social preferences and opinions before the establishment of LEZ, could help investigate the relation between the level of restrictions and behavioral adoption of the residents and car users. It is also recommended to take a lesson from the zones already existing in other cities and to follow the solutions that have occurred to meet the expectations of the society while leading to lower GHG emissions and higher standard of living.